TINJAUAN PELAKSANAAN PEKERJAAN PONDASI BORED PILE ABUTMENT 1 PADA PROYEK PEMBANGUNAN FLY OVER GELUMBANG - Wianto, M. Arpando Eko; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
A bored pile foundation is a deep foundation that has a tube-like shape and is made from a reinforced concrete mixture with certain diameter dimensions. Bored piles can be installed into the ground by drilling the ground first, then filling with reinforcement and casting concrete. The function of the foundation is to place the building and transmit the distributed load, so the foundation structure of the bottom of the building is directly connected to the ground and functions to support all loads, both live loads and dead loads above it and external forces. This flyover is a substructure work, including bored pile foundations, abutments and pillars. One of the most important structural parts is the foundation on the bored pile.Keywords: Bored Pile Foundation for Fly Over construction